Determinan Status Gizi Kurang Pada Balita Di Puskesmas Belawan Kota Medan - Duma Jerriyah Harahap; Zuraidah Nasution; Aida Fitria (JURNAL BIDANG ILMU KESEHATAN, 2019)
Introduction: According to the observation on nutritional status in Indonesia in 2017, underweight status in balita (below five year-old children) per age was 17.8%. Objective: The study was to find out the determinants nutritional deficiency status in balita in balita at Belawan Puskesmas, Medan, in 2018. Method: The research used mixed method with sequential explanatory and quantitative approach and case-control design. The samples were 24 balita who were 12-24 month-old in the case group and 24 balita in the control group. The data were gathered by conducting in-depth interview with 5 informants. Result: OR-values of infection = 5.32, history of breastfeeding with exclusive breast milk =6.333, and family income = 9.308, the number of family members = 4.200, women’s knowledge of nutritional deficiency = 6.333, and eating habit = 7.286. Eating habit was the determinant factor at Exp (β) = 11.400. Qualitative approach indicated that the variables of care pattern of feeding and health care in balita and husbands’ role were the determinants of nutritional deficiency status in balita. Conclusion: Eating habit, care pattern of feeding and health care, and husbands’ role were the determinants of nutritional deficiency in balita. Keywords: Nutritional deficiency status, balita